EFFECTIVENESS OF THE IMPLEMENTATION OF THE EMPLOYEE ABSENCE INFORMATION SYSTEM (SIAP) IN IMPROVING EMPLOYEE WORK DISCIPLINE (Study at the Food Security, Agriculture, and Fisheries Service of Probolinggo City) - Dina Agustin Anggraini Sutomo; Veronica Sri Astuti Nawangsih; Mastina Maksin (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This study examines the effectiveness of the implementation of the Employee Attendance Information System (SIAP) in improving employee work discipline. The focus of this study is based on the effectiveness theory developed by Sutrisno (2007) which consists of five indicators and there are supporting and inhibiting factors. With this system, it provides convenience in the process of employee attendance in conducting absences or presence during working hours. However, in practice, there are still obstacles related to the implementation of SIAP in the work environment of the Food Security, Agriculture, and Fisheries Service. This study uses a qualitative approach with a purposive sampling data collection technique with the criteria of informants who are users of the SIAP application. Data were obtained through observation, interviews, and documentation in obtaining data in the field and analyzed through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the SIAP application is considered quite effective, referring to the effectiveness theory with five indicators by Sutrisno (2007) through program understanding, on target, on time, achievement of goals, and real change. From the informant's statement, the application of the SIAP application in employee attendance is considered quite effective, this is proven by the achievement of timely indicators that assess the SIAP application sometimes has obstacles such as a system that often errors. In addition to supporting factors, there are also inhibiting factors such as accuracy in the accuracy system of the application in adjusting coordinate points when taking attendance. From the research conducted by researchers, it can be concluded that the application of the SIAP application is considered quite effective because deficiencies are still found in the SIAP application. Thus, the recommendations provided by researchers can be used as a means or improvement to the SIAP system or application with the aim of increasing employee work discipline.